Association of complement components with the risk and severity of NAFLD: A systematic review and meta-analysis - Zhao, Jianbo; Wu, Yafei; Lu, Peng; Wu, Xiaoqin; Han, Junming; Shi, Yingzhou; Liu, Yue; Cheng, Yiping; Gao, Ling; Zhao, Jiajun; Wang, Zhen; Fan, Xiude (Frontiers in Immunology, 2022)
Background It is generally believed that complement system is strongly associated with the risk of nonalcoholic fatty liver disease (NAFLD). However, complement system contains a variety of complement components, and the relationship between complement components and the risk and severity of NAFLD is inconsistent. The aim of this meta-analysis was to evaluate the association of complement components with the risk and severity of NAFLD. Methods We searched PubMed, Embase, Cochrane Library, Google Scholar, Scopus, and ZhiWang Chinese databases from inception to May 2022 for observational studies reporting the risk of NAFLD with complement components. Random-effects meta-analysis was used to obtain pooled estimates of the effect due to heterogeneity. Results We identified 18 studies with a total of 18560 included subjects. According to recent studies, levels of complement component 3 (C3) (mean difference (MD): 0.43, 95% confidence interval (CI) 0.26-0.60), complement component 4 (C4) (MD: 0.04, 95% CI 0.02-0.07), complement component 5(C5) (MD: 34.03, 95% CI 30.80-37.27), complement factor B (CFB) (MD: 0.22, 95% CI 0.13-0.31) and acylation stimulating protein (ASP) (standard mean difference (SMD): 5.17, 95% CI 2.57-7.77) in patients with NAFLD were significantly higher than those in the control group. However, no statistical significance was obtained in complement factor D (CFD) levels between NAFLD and non-NAFLD (MD=156.51, 95% CI -59.38-372.40). Moreover, the levels of C3, C5, CFB, and ASP in patients with moderate and severe NAFLD were significantly higher than those in patients with mild NAFLD. Except for C4 and CFD, the included studies did not explore the changes in the severity of NAFLD according to the concentration of C4 and CFD. Conclusions This meta-analysis demonstrates that an increase in complement components including C3, C5, CFB, and ASP is associated with an increased risk and severity of NAFLD, indicating that they may be good biomarkers and targets for the diagnosis and treatment of NAFLD. Systematic review registration PROSPERO [https://www.crd.york.ac.uk/PROSPERO/], identifier CRD42022348650.